THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF UZBEK LANGUAGE - A. Usmanov (Modern American Journals, 2026)
Artificial intelligence technologies are revolutionizing the development of languages in the modern world, in particular the Uzbek language, as they consolidate the position of the language in digital environment through national language models, automated translation and speech synthesis systems. This article examines in detail the role of artificial intelligence in expanding the lexical richness of the Uzbek language, analyzing the grammatical structure and pragmatic application of the Uzbek language, as well as discussing in detail practical projects and international experience in Uzbekistan.